Multiferroism and colossal magneto-capacitance effect of La0.2Pb0.7Fe12O19 ceramics. (December 2016) - Tan, Guo-Long; Sheng, Hao-Hao
Abstract: Multiferroic materials with such magnetoelectric properties that are comparable to the useful ferroelectrics and ferromagnets are exceedingly rare. We report here on integration of ferroelectricity and ferromagnetism in a M-hexaferrite (La0.2 Pb0.7 Fe12 O19 ), which simultaneously exhibits colossal magnetocapacitance effect at room temperature. The coexistence of the off-centered FeO6 octahedron and electron spins in partially filled Fe 3d or La 3f orbits is supposed to be responsible for mergence of mutually exclusive electric and magnetic orders. Five magnetoelectric phases and boundaries have been built up by the permeability profile. By applying a magnetic field (B), the capacity or dielectric constant demonstrates giant oscillations, whose maximum amplitude exceeds 1.90 × 10 5 % at 80 Hz. The huge oscillations are associated with the variable component and orientation of the cycloid conic spins at the boundaries between two neighboring magnetic phases, where the cycloid cone axes align themselves parallel or reversal parallel to the direction of B field. Thus the dielectric constants are systematically enhanced to reach a giant value of ε m ± ′ = +58270 or −84866 due to the great promotion of spin-current induced polarization. Graphical abstract: Colossal magnetocapacitance effect of the La0.2 Pb0.7 Fe12 O19 ceramic: Oscillation of relative dielectric constant (or capacity) with magnetic field for the polycrystalline La0.2 Pb0.7 Fe12 O19 ceramics at room temperature, the insets display the cycloid conical spin structures with positive Mc (left) and negative Mc (right), Mc is the spin-current induced polarization. Image 1